Challenges and prospects of parental involvement in the teaching and learning in early childhood education - Mlilo, Sikhangezile (Midlands State University, 2018)
The study aimed at finding out the challenges and prospects about parental involvement in teaching and learning at Early Childhood Education level. The study employed a qualitative research approach and adopted a descriptive survey design. The population of the study consisted of ten schools in Hyde Park North cluster under Khami District in Bulawayo Metropolitan. A sample consisted of eighteen participants from three primary schools who were purposively chosen. The participants included three teacher in charge from the selected schools, six Early Childhood Education teachers and nine Early Childhood Education parents of which there were three from each school. Questionnaires, interviews and observation were used to collect data for the study. The study revealed that parents are involved in children's education in the selected schools. However, there were challenges that hindered parental involvement such as work and financial constraints, negative attitudes of both teachers and parents, language and culture. As a result these challenge hindered effective parental involvement in schools. Though there were challenges in involving parents in Early Childhood Education, the study recommended that there is need to invite parents to school meetings in order to educate them on the importance of working together with the school for the benefit of the learner. Programmes such as consultation, graduation, toy making sessions and sporting activities should be employed as a way of engaging parents in school programmes. The study also recommended that teachers need to improve their communication with parents regarding activities taking place in schools.